Severity of visual impairment and depression among elderly Malaysians - Noran, N.H.; Izzuna, M.G.; Bulgiba, Awang; Mimiwati, Z.; Ayu, S.M. (SAGE Publications, 2009)
Objective. This study aimed at evaluating the relationship between severity of visual impairment and depression among elderly Malaysians attending an eye clinic. Methods. This was a cross-sectional study. The study population included patients, aged >= 60 years who attended the Eye Clinic in University Malaya Medical Centre. Exposure measurement was based on ophthalmologic examinations by an ophthalmologist. Data on outcome were measured using the Geriatric Depression Scale. Results. After adjusting for important confounders, severity of visual impairment either having low vision or blind were independent risk factors of depression. The odds of developing depression among elderly with low vision were 2 times more than those with normal vision, and elderly who were blind had almost 5 times the odds to be depressed compared with those having normal vision. Conclusion. Findings from this study suggest a positive relationship between the severity of visual impairment and depression among elderly Malaysians.